Lanza's mob: the Mafia and San Francisco - DiEdoardo, Christina Ann-Marie (Praeger, 2016)
Disarming the bodyguard: San Francisco mafia myths and realities -- Sicilian realities and American dreams -- To the mean streets of New York -- Go West, young man, cause it's prohibition -- Ferri meets his maker -- The end of Prohibition and the big strike -- Marone, we can't use the wharf no more -- DeJohn takes the big sleep -- The Kefauver show -- The Apalachin debacle -- From anonymity to "top hoodlum" -- Legitimate businesses -- The swinging 1960s -- Epilogue